2009
DOI: 10.1038/nrcardio.2009.34
|View full text |Cite
|
Sign up to set email alerts
|

First case of stenting of a vulnerable plaque in the SECRITT I trial—the dawn of a new era?

Abstract: Six months of follow-up has demonstrated that a patient with an IVUS-derived, thin capped fibroatheroma was successfully treated with a stent tailored to shield vulnerable plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 21 publications
(16 reference statements)
0
21
0
Order By: Relevance
“…It was proposed that the growth of neointima tissue on the top of a vulnerable plaque might increase the thickness of the fibrous cap [103,110,111]. Brugaletta et al [112] reported the ability of bioresorbable vascular scaffold (BVS) implantation to promote the growth of neointimal tissue, which acts as a barrier to isolate vulnerable plaques.…”
Section: Optimizing Percutaneous Coronary Intervention Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that the growth of neointima tissue on the top of a vulnerable plaque might increase the thickness of the fibrous cap [103,110,111]. Brugaletta et al [112] reported the ability of bioresorbable vascular scaffold (BVS) implantation to promote the growth of neointimal tissue, which acts as a barrier to isolate vulnerable plaques.…”
Section: Optimizing Percutaneous Coronary Intervention Proceduresmentioning
confidence: 99%
“…The NIRS lipid signal could not distinguish neoatherosclerosis from fibroatheroma underlying the stent. No doubt that NIRS can detect coronary LCP, but it seems unlikely suitable as a standalone technique for accurate neoatherosclerosis detection and that the adjunction of IVUS or OCT will be required to determine the position of NIRS lipid signal relative to the underlying stent struts [110].…”
Section: Optimizing Percutaneous Coronary Intervention Proceduresmentioning
confidence: 99%
“…Currently, local therapy for potentially vulnerable plaques is not recommended because of lack of evidence of efficacy, 12 although pilot studies using a "luminal shield" to stabilize VH-IVUSdefined vulnerable plaques have been positive. 13 A widespread change in clinical practice would require that VH-IVUS plaque classification does not vary significantly between operators, and is similar to core-laboratory analysis used for VH-IVUS validation.…”
Section: Clinical Perspective On P 93mentioning
confidence: 99%
“…A new stent design with self-expanding, ultrathin struts is currently being evaluated in patients with nonobstructive TCFA, with encouraging preliminary results. 20 If proven to be of significant value, this invasive approach may well be considered as a complementary treatment strategy for patients diagnosed with high-risk TCFA by noninvasive methods. Only strict, randomized clinical studies may help us to elucidate this issue.…”
Section: What Is Next?mentioning
confidence: 99%